Low-energy high-current electron beam generation in plasma system and beam-plasma interaction - Agafonov, A.V.; Bogachenkov, V.A.; Suleymanov, O.S.; Tarakanov, V.P. (Вопросы атомной науки и техники, 2007)
The review of results of experimental investigations and computer simulations of low-energy high-current electron beam generation in a low-impedance system and dynamics of beam-plasma system are given. The system includes a long plasma-filled diode, an auxiliary thermionic cathode and an explosive emission cathode. The auxiliary cathode is used to generate a low-current, low-voltage electron beam to form long plasma anode by means of a residual gas ionisation in an external longitudinal magnetic field. The high-current low-energy electron beam is generated from the explosive emission cathode embedded in preliminary prepared plasma. Peculiarities of the system are due to: 1) the generation of electron beams with currents exceeding Alfven’s limit; 2) the charge density of the beam close to the plasma density. These peculiarities complicate beam-plasma interaction significantly due to sharp non-uniform distribution of the beam current density, dominant transverse motion of the beam electrons and redistribution of ion-plasma density under the influence of fields. Computer simulation was performed using electromagnetic PIC code KARAT for different geometry’s of the system.